2015
DOI: 10.4314/ejbe.v4i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Levels of Agricultural Development Agents Job Satisfaction: The Case of Kalu Woreda, South Wollo Zone of the Amhara National Regional State

Abstract: This study was conducted with an objective of assessing the level of job satisfaction and its determinants among agricultural development agents working in different kebeles of Kalu Woreda, South Wollo Zone of the Amhara National Regional State. A total of 100 development agents were selected and interviewed using simple random sampling technique to collect data for the study through structured questionnaire. Descriptive and multiple regression methods were used to address the study objectives. Results of desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The results showed that training had a significant positive effect on job satisfaction. The results of this study are consistent with previous studies shown by (Awan, Rizwan, Razzaq, & Ali, 2014;Hanaysha & Tahir, 2016;Kelemu, Sime, & Zalalam, 2015;Khan, Arif, & Rehman, 2015;Msuya et al, 2017;Wang, Tang, Zhao, Meng, & Liu, 2017).…”
Section: The Effect Of Training On Job Satisfactionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that training had a significant positive effect on job satisfaction. The results of this study are consistent with previous studies shown by (Awan, Rizwan, Razzaq, & Ali, 2014;Hanaysha & Tahir, 2016;Kelemu, Sime, & Zalalam, 2015;Khan, Arif, & Rehman, 2015;Msuya et al, 2017;Wang, Tang, Zhao, Meng, & Liu, 2017).…”
Section: The Effect Of Training On Job Satisfactionsupporting
confidence: 93%
“…Based on the linkages described above, the researcher tries to close the gap on the inconsistency of the results between training and personality on employee performance by looking at the relationship between the two and job satisfaction. The results of the study (Hanaysha & Tahir, 2016;Kelemu, Sime, & Zalalam, 2015;Msuya et al, 2017) state that training has a significant effect on job satisfaction. By finding a link between job satisfaction and employee performance and a significant relationship between training variables and job satisfaction, the researchers made job satisfaction a variable that mediates the relationship between training and employee performance.…”
Section: Introductionmentioning
confidence: 97%
“…This finding is in line with that of Wang et al (2017), who stated that training can increase employee satisfaction. Attention is necessarily paid to allowing training opportunities and career paths to enhance job satisfaction of agricultural extension agents (Catherine et al, 2017 andKelemu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, observational studies conducted in low-income countries indicate that extension offices are often understaffed and that agents are often underqualified and unmotivated. Low morale, absenteeism, and high turnover are commonly reported among agricultural EAs (Davis et al 2012;Feder et al 2010;Kassa 2002;Kassa & Abebaw 2004;Kelemu, Sime, & Hailu 2014;Ragasa et al 2016). This problem is particularly severe in remote areas, where quality extension services are much more needed (Davis et al 2009;Ragasa et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the design of these interventions has not been grounded in systematic studies of the responsiveness of EAs to them. Moreover, the policy initiatives taken so far do not seem to have abated many of the problems EAs face, as rapid turnover of EAs persists, especially in remote rural areas (ATA 2017;Davis et al 2010;Haile & Abebaw 2012;Kelemu et al 2014). This suggests the need to study the nature and determinants of EAs' preference for job attributes and their labor supply choices to better design more effective policy interventions that can incentivize and retain EAs, in particular; and public workers in remote areas in general.…”
Section: Introductionmentioning
confidence: 99%